(untitled) (World Bulletin of Social Sciences, 2026)
In this article, specific requirements for pedagogical technologies to achieve the idea of academic freedom are analyzed in detail. Academic freedom is essentially liberal democratic views, their connection with education and training, pedagogical research is revealed. Also, the formation of university education pedagogy of higher education, which is sharply different from school and preschool education, is subject (professor, teacher, educator) and object (student, pupil, detailed information about the construction of the relationship between the student (student) into dialogue, trust in each other, the pedtechnology of encouraging the object to work on itself, to create new things is given.